Enhancement of Teacher Knowledge in Making ICT-Based Chemistry Learning Media with emphasis on Three Levels of Representation - minda - azhar; Alizar - Ulianas; Miftahul - Khair; Hutdia Putri M; Natia Afriana S; zulhendra - Zulhendra (Fakultas MIPA Universitas Negeri Padang, 2019)
Abstract - The use of three levels of chemical representation and interconnection is needed to understand the chemical concepts as a whole. The purpose of service activities is to increase teacher knowledge in making ICT-based chemical learning media with emphasis on three level representation. The solution given is giving training to the teacher. In this training, were used lecture and demonstration methods and practices. The results of the service activities can improve the knowledge and skills of chemistry teachers using standard general chemistry e-books and chemistry learning videos on websites on the internet. This service activity can improve the knowledge and skills of chemistry teachers to integrate these learning resources for the manufacture of ICT-based chemistry learning media with an emphasis on interconnecting of three-levels representation. This service activity also increases teacher knowledge about mental models and how to measure them.